2010
DOI: 10.3109/13693780903514880
|View full text |Cite
|
Sign up to set email alerts
|

Human external ear canal as the specific reservoir ofMalassezia slooffiae

Abstract: The incidence of Malassezia species recovered from the external ear canal was characterized using culture medium optimized for Malassezia spp., CHROMagar Malassezia. The results of this study indicated that in healthy individuals M. slooffiae was the dominant Malassezia species followed by M. restricta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Recently, two interesting studies have been published, one showing that M. slooffiae is abundant in the human external auditory canal (21), and the other showing that M. slooffiae may cause otitis externa (22). In the present study, we showed by the highly accurate techniques of real鈥恡ime PCR and rRNA clone library analysis that M. slooffiae is the predominant species in both the external auditory canal and on the sole of the foot.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two interesting studies have been published, one showing that M. slooffiae is abundant in the human external auditory canal (21), and the other showing that M. slooffiae may cause otitis externa (22). In the present study, we showed by the highly accurate techniques of real鈥恡ime PCR and rRNA clone library analysis that M. slooffiae is the predominant species in both the external auditory canal and on the sole of the foot.…”
Section: Discussionmentioning
confidence: 99%
“…More than 20 studies (Tables 3 to 6) have been carried out worldwide on the epidemiology of Malassezia species in cases of pityriasis versicolor, seborrheic dermatitis, atopic eczema, and psoriasis and on healthy control skin of the same individuals or skin from healthy volunteers (53,63,89,112,122,146,171,173,180,185,228,237,255,259,275,286,344,353). Results are not directly comparable between studies, as different methodologies, isolation media, and identification procedures have been employed.…”
Section: Culture-based Epidemiologymentioning
confidence: 99%
“…Shiota et al (2009) reported the presence of this yeast in 5 of 63 patients with otitis (Shiota et al, 2009). The presence of M. slooffiae and M. restricta in the external auditory canal of clinically healthy people (Kaneko et al, 2010) while presence of M. sympodialis in a diabetic patient with external otitis has also been reported (Chai et al, 2000). Sugita et al (2013) reported the presence of M. globosa and M. restricta in lesions of the external auditory canal and sole of the foot (Sugita et al, 2013, Zhang et al, 2012.…”
Section: Discussionmentioning
confidence: 96%
“…However, there are few reports of this yeast in human cases of external otitis (Kaneko et al, 2010) and no reports of lipophilic Malassezia as causing agent of otitis media in infants and adults. Therefore, the aim of this work was to report the isolation and identification of Malassezia by PCR amplification and sequencing of the D1/D2 region of DNA encoding the LSU rRNA in two infants with a clinical diagnosis of otitis media.…”
mentioning
confidence: 99%